Professional governance for nursing : the framework for accountability, engagement, and excellence - Start, Rachel; Hancock, Beverly; Porter-O'Grady, Timothy (Burlington, MA : World Headquarters, 2025)
"Nursing leadership needs a common framework in which to voice their problems and solutions, form policy, and make decisions that have a clear effect on their work environment. Published in partnership with AONL, Professional Governance for Nursing: The Framework for Accountability, Engagement, and Excellence is a comprehensive book about professional nursing governance covering concepts, roles, and application to support students and professionals across all settings and roles where nurses work in addressing contemporary issues affecting the profession now and in the future. It covers all potential practice settings and focuses on providing the structure and examples of related behavior that exemplify professional practice"--Provided by publisher.
Includes index.
Keywords: Nursing, Supervisory -- organization & administration; Nursing staff -- organization & administration; Nursing Services -- organization & administration; Leadership; Professionalism